2020
DOI: 10.21203/rs.2.18864/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A nationwide survey on the use of Heated Humidified High Flow Oxygen therapy on the paediatric wards in the UK: Current practice and research priorities

Abstract: Background: Heated Humidified High Flow Nasal Cannula Oxygen Therapy (HHFNC) is increasingly used on the paediatric wards and High Dependency Units (HDU) for different types of pathologies and different age groups. We aimed to describe current practice related to the use of HHFNC on the paediatric wards and HDUs, weaning practices and preferred outcome measures for future research. Methods: We carried out a cross-sectional online survey of UK paediatric consultants or their delegates working on the paediatric… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…In these studies, a beneficial role for the use of HFNC in the general pediatric ward to prevent of PICU admissions is suggested (19,20), but the effectiveness of preventing PICU admission and intubation rates is under discussion [19,20]. A recent survey in the UK indicated however that treating pediatricians prefer HFNC over CPAP as being more effective with fewer complications [21] In our study, we did not find a decrease in PICU admissions for RSV bronchiolitis after the introduction of HFNC in 2009, precluding any conclusions on the effectiveness of HFNC in the prevention of escalation of respiratory support [19,20]. Although current study was not designed to investigate the effectiveness of HFNC, our observation of the increased burden of RSV-bronchiolitis for the PICU concomitantly with the wide-scale introduction of HFNC warrants future research on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, a beneficial role for the use of HFNC in the general pediatric ward to prevent of PICU admissions is suggested (19,20), but the effectiveness of preventing PICU admission and intubation rates is under discussion [19,20]. A recent survey in the UK indicated however that treating pediatricians prefer HFNC over CPAP as being more effective with fewer complications [21] In our study, we did not find a decrease in PICU admissions for RSV bronchiolitis after the introduction of HFNC in 2009, precluding any conclusions on the effectiveness of HFNC in the prevention of escalation of respiratory support [19,20]. Although current study was not designed to investigate the effectiveness of HFNC, our observation of the increased burden of RSV-bronchiolitis for the PICU concomitantly with the wide-scale introduction of HFNC warrants future research on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Several national and multinational surveys have demonstrated that pediatric intensivists currently select HFNC for initial respiratory care in cases of severe bronchiolitis 18,19 . This popularity among caregivers appears to be associated with the perception of a technique that is easy to implement, with comparable effectiveness and fewer complications than CPAP 20 . The physiological background for using CPAP in this instance is that the application of nearly constant pressure support is associated with rapid unloading of respiratory muscles, increased expiratory time, and concomitantly improved respiratory distress 4,11,21 .…”
Section: Oxygen Low Flow Hfnc (2 L/kg/min) Cpap (7 CM H2o) Niv‐ps Nivmentioning
confidence: 99%